Interest and Science Process Skills in Science Education Based on Gender - Budiarti, Retni Sulistiyoning; Kurniawan, Dwi Agus; Perdana, Rahmat; Septi, Sabila Eka (Jurnal Pendidikan dan Pengajaran, 2022)
The urgency of this research is very important because there is no research that examines student interests and science process skills in detail based on grade level and gender in a school. In addition, this research needs to be done to find out the interests and skills of the science process in more depth based on the indicators tested. The purpose of this research is (1) to find out how the comparison of interest between women and men in science subjects. (2) to find out the comparison of science process skills in female and male students towards science subjects. (3) to find out how the relationship between interest and science process skills in students with science subjects. This study uses a quantitative method with a comparative type. Quantitative research is a field of inquiry that stands alone, is scientific in nature and aims to understand social reality. The instrument in this study used a questionnaire and an observation sheet, namely a student interest questionnaire and an observation sheet for science process skills. Based on the results of hypothesis testing, research testing and data analysis, the conclusion of this study is from the T test there are differences in the interests of female students and male students in class VII A and VII B. From the results of the T test for students' science process skills there are differences in the interests of female students and male students in grades VII A and VII B. Based on the results of the correlation test between interests and science process skills of grade VII A students there is a relationship between interests and science process skills between female and male students as well as in class VII B. Students' interest and science process skills have a significant influence on curiosity, learning materials and teacher attitudes, student observation and communication.